Effects of Full-Moon Definition on Psychiatric Emergency Department Presentations. (12th January 2014) - Parmar, Varinder S.; Talikowska-Szymczak, Ewa; Downs, Emily; Szymczak, Peter; Meiklejohn, Erin; Groll, Dianne
Abstract : Objectives . The lunar cycle is believed to be related to psychiatric episodes and emergency department (ED) admissions. This belief is held by both mental health professionals and the general population. Previous studies analyzing the lunar effect have yielded inconsistent results. Methods . ED records from two tertiary care hospitals were used to assess the impact of three different definitions of the full-moon period, commonly found in the literature. The full-moon definitions used in this study were 6 hours before and 6 hours after the full moon (a 12-hour model); 12 hours before and 12 hours after the full moon (a 24-hour model); and 24 hours before and after the day of the full moon (a 3-day model). Results . Different significant results were found for each full-moon model. Significantly fewer patients with anxiety disorders presented during the 12-hour and 24-hour models; however, this was not true of the 3-day model. For the 24-hour model, significantly, more patients presented with a diagnosis of personality disorders. Patients also presented with more urgent triage scores during this period. In the 3-day model, no significant differences were found between the full-moon presentations and the non-full-moon presentations. Conclusions . The discrepancies in the findings of full moon studies may relate to different definitions of "full moon." The definition of the "full moon" should be standardized for future research.